DESENVOLVIMENTO DO WEB APP NUTRIAÇÃO DE BOLSO PARA PROFISSIONAIS DA ATENÇÃO PRIMÁRIA À SAÚDE NO CUIDADO NUTRICIONAL DE CONDIÇÕES CRÔNICAS - GABRIEL BARBOSA DELMONDES DE MORAES (2022)
INTRODUCTION: The alarming prevalence of Chronic Non-Communicable Diseases (NCDs) generate overburden on health teams and high costs to public coffers. Despite having at their disposal a valuable range of instructional and support materials, health professionals lack tools that facilitate their routine of preparing health actions and Food and Nutritional Surveillance (VAN). Therefore, this study aimed to build the web app "Nutriação de Bolso", in order to assist in the execution of actions in food and nutrition in Primary Health Care (PHC) and in the improvement of VAN. METHODS: Action research, through a descriptive study, based on secondary data, with a qualitative approach. The first step consisted of analyzing VAN coverage in Campo Grande/MS, as a strategy to document the diagnosis of VAN coverage and detect gaps to be filled with the use of the web app locally. Then, the technical-scientific content of the web app was determined, a stage in which the use of the Brazilian Ministry of Health's "Matrix for Organization of Food and Nutrition Care in PHC" was determined. Finally, the software was architected in the web app format, using PHP 8.1.x, MySQL 8.0.x, Nginx and Ubuntu 22.04 technologies, for later deployment on the Mato Grosso do Sul State Department of Health (SES/MS) website, via official signed agreement. RESULTS: The analysis of VAN coverage in Campo Grande/MS enabled the identification of existing gaps in the process of reading reports and registering data from e-SUS, especially when compared to data from SISVAN Web. “Nutriação de Bolso” was developed in a format like a flowchart, in which the health professional has the “universal practices” and “specific practices” buttons available on the main screen. Universal practices are organized to suggest actions to serve the general population, while specific practices are organized to consolidate the contents for specific populations, such as age groups and traditional people. In this way, the health professional has the possibility to find, in an agile and intuitive way, the action recommendation that corresponds to his demand at the time of individual or collective care, in addition to having a quick guidance on how to correctly carry out the VAN work in APS. CONCLUSION: The analysis of VAN coverage in Campo Grande/MS proved to be satisfactory, especially when compared to other regions of Brazil, but there are obstacles to be overcome in this process, such as the e-SUS reports, which are characterized as challenging and inefficient for outline strategies to improve the assessment of nutritional status in the service. Therefore, the use of Nutriação de Bolso by health professionals is encouraged here, in orderd to train their skills regarding food and nutrition in their work in PHC.